A method for preparing polyethylene glycol solid-solid phase change material
By introducing poly(2-vinyl)ethylene glycol units into polyethylene glycol and building a crosslinking network structure, combining UV photocuring crosslinking materials with polythiol compounds, the problem of difficult balance between thermal storage capacity and mechanical properties of polyethylene glycol solid-solid phase change materials is solved, and the effects of high thermal storage capacity, excellent mechanical properties and good thermal stability are achieved.
Patent Information
- Application Number
- CN202411686013.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-24
- Publication Date
- 2025-04-01
AI Technical Summary
The existing polyethylene glycol solid-solid phase change materials are difficult to balance between heat storage capacity and mechanical properties, and the thermal stability is insufficient, so they cannot meet the application needs in high-strength and complex environments.
By introducing poly(2-vinyl)ethylene glycol units into polyethylene glycol, a polyethylene glycol-poly(2-vinyl)ethylene glycol copolymer with a crosslinking network structure is constructed, and the crosslinking material is cured with a UV photocuring crosslinking material composed of polythiol compounds to improve the crosslinking density and thermal stability of the material.
It realizes the high heat storage ability, excellent mechanical properties and good thermal stability of polyethylene glycol solid-solid phase change materials, and can show stable performance in high strength and complex environments.
Smart Images

Figure CN119735831A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of radiation curing materials and relates to a method for preparing a polyethylene glycol solid-solid phase change material. Background Art
[0002] Solid-solid phase change materials (SSPCMs), as a new type of heat storage material, have attracted widespread attention due to their potential applications in battery thermal management systems, solar energy storage, and building energy conservation. Among many SSPCMs, polyethylene glycol (PEG) has become a promising candidate material for SSPCMs due to its adjustable phase change temperature, high latent heat enthalpy, good thermal properties, and good compatibility and biocompatibility (Adv. Mater., 2022, 34, 2202457; J. Energy Storage, 2024, 89.). The preparation methods of PEG-SSPCMs are mainly divided into chemical grafting, block copolymerization, cross-linking polymerization, and physical encapsulation. SSPCMs prepared by covalent cross-linking PEG are a better choice to solve the leakage problem. Compared with other methods, chemical cross-linking has better thermal cycling stability (Chem. Eng. J., 2022, 429: 132447; Chem. Eng. J., 2020, 390: 124586.).
[0003] A common cross-linking PEG method is to introduce cross-linkable terminal groups into the PCL precursor, such as triethoxysilane, diethanol groups, etc., or to prepare it into a cross-linked polyurethane material. (Chem. Eng. J. 2023, 462, 142164; ACS Appl. Mater. Interfaces, 2023, 15, 8613-48622.). However, the current strategy can only introduce a cross-linkable group (such as triethoxysilane) at the end of PEG, resulting in a low cross-linking density of the material and poor mechanical properties (elongation at break <5%) (Adv. Funct. Mater. 2022, 32, 2108000). Although the mechanical properties can be improved by reducing the molecular weight of polyethylene glycol or preparing it into polyurethane and then cross-linking it, it will lead to a decrease in heat storage capacity. Balancing PEG content and cross-linking density is crucial for designing SSPCMs with both high energy storage capacity and mechanical properties. Currently, there are few studies on adjusting the PEG content and cross-linking density to achieve a balance between mechanical properties and thermal storage properties, and achieving this goal is of great significance.
[0004] Faced with the challenges of balancing the heat storage capacity, mechanical properties and thermal stability of SSPCMs in practical applications, we successfully constructed SSPCMs with a cross-linked network structure by introducing a series of poly(2-vinyl) glycol units at the end of polyethylene glycol polyols through allyl etherification. This strategy aims to prepare SSPCMs with good mechanical properties, heat storage capacity and thermal stability to meet the application needs of SSPCMs in high-intensity and complex environments. Summary of the invention
[0005] In view of the defects in the prior art, the first aspect of the present invention aims to provide a polyethylene glycol solid-solid phase change material having good heat storage capacity, mechanical properties and thermal stability.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A polyethylene glycol solid-solid phase change material, characterized in that the solid-solid phase change material is a UV light-cured cross-linked material formed by a polyethylene glycol-poly (2-vinyl) glycol copolymer and a polythiol compound.
[0008] Further:
[0009] The polyethylene glycol-poly (2-vinyl) glycol copolymer has a structure shown in the following general formula:
[0010]
[0011] Wherein: m, n1 and n2 are all positive integers, and m, n1 and n2 ≥ 1.
[0012] The polyethylene glycol-poly (2-vinyl) glycol copolymer can be prepared by the following method: polyethylene glycol containing two hydroxyl groups and 4-vinyl-1,3-dioxolane-2-one or vinyl oxirane are used as raw materials, dissolved in an organic solvent, and reacted at 10-70° C. for 1-6 hours in the presence of a palladium catalyst and a phosphine ligand to obtain the polyethylene glycol-poly (2-vinyl) glycol copolymer.
[0013] The polyethylene glycol has a molecular weight of one or more of 500, 1000, 2000, 4000, 6000, 8000, 10000 or 20000; preferably, the polyethylene glycol is selected from polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000 and polyethylene glycol 10000.
[0014] The second aspect of the present invention aims to provide a method for preparing a polyethylene glycol solid-solid phase change material, characterized in that it comprises the following steps: taking the following raw materials by mass fraction, mixing them and reacting them under UV irradiation for 1-100 minutes to obtain a polyethylene glycol solid-solid phase change material;
[0015] 80-95 parts of polyethylene glycol-poly (2-vinyl) glycol copolymer
[0016] 3-15 parts of polythiol compound
[0017] 2 to 5 parts of photoinitiator.
[0018] Further:
[0019] The polythiol compound is selected from one of pentaerythritol tetrakis(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), and 1,4-butanediol bis(thioglycolate).
[0020] The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0021] The beneficial effects produced by the present invention include:
[0022] A polyethylene glycol solid-solid phase change material prepared by the present invention has a curing system composed of a polyethylene glycol-poly (2-vinyl) glycol copolymer and a multifunctional thiol compound, which can improve the problem that the heat storage capacity and mechanical properties of the polyethylene glycol solid-solid phase change material are difficult to balance, and a larger functional group structure can realize a polymer network with a higher cross-linking density, which can ensure that the solid-solid phase change material has good thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the NMR spectrum of the polyethylene glycol 10000-poly(2-vinyl)ethylene glycol copolymer P1 prepared in the example.
[0024] Figure 2 This is the NMR spectrum of the polyethylene glycol 10000-poly(2-vinyl)ethylene glycol copolymer P2 prepared in the example.
[0025] Figure 3 This is the NMR spectrum of the polyethylene glycol 10000-poly(2-vinyl)ethylene glycol copolymer P3 prepared in the example.
[0026] Figure 4 This is the NMR spectrum of the polyethylene glycol 8000-poly(2-vinyl)ethylene glycol copolymer P4 prepared in Example.
[0027] Figure 5 This is the NMR spectrum of the polyethylene glycol 6000-poly(2-vinyl)ethylene glycol copolymer P5 prepared in the example.
[0028] Figure 6 This is the NMR spectrum of polyethylene glycol 4000-poly(2-vinyl)ethylene glycol copolymer P6 prepared in the example.
[0029] Figure 7 This is the infrared spectrum of the polyethylene glycol solid-solid phase change material prepared in Example. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0031] The polyethylene glycol 10000-poly (2-vinyl) glycol copolymer used in the embodiment of the present invention can be prepared by the following method:
[0032] Preparation of polyethylene glycol 10000-poly (2-vinyl) glycol copolymer P1
[0033] Polyethylene glycol 10000 (60.0 g, 6 mmol, Mn: 12600, Mw / Mn: 1.06), tri(dibenzylideneacetone)dipalladium(0)-chloroform adduct (46.7 mg, 0.15 mol% for VEC), and phosphine ligand bis(2-diphenylphosphinophenyl)ether (48.4 mg, 0.3 mol% for VEC) were added into the reactor, vacuum dehydrated, and replaced with N2 three times, BEt3 (90 μL of 1 mol·L-1 in THF solution, 0.3 mol% for VEC) and 120 mL of solvent dichloromethane were added, and after the polyethylene glycol was dissolved, 4-vinyl-1,3-dioxolane-2-one (3423.0 mg, 30 mmol, 5 eq.) was added, and the reaction was controlled at 10°C and stirred for 6 hours. After the reaction, the catalyst and the phosphine ligand were removed to obtain a polyethylene glycol-poly(2-vinyl)ethylene glycol copolymer labeled as P1 with a yield of 92%, a vinyl content of 0.23±0.02 mmol / g, a number average molecular weight Mn: 12800, and a polydispersity Mw / Mn: 1.06.
[0034] The NMR spectrum of polyethylene glycol 10000-poly (2-vinyl) glycol copolymer P1 is as follows Figure 1 shown.
[0035] Preparation of polyethylene glycol-poly (2-vinyl) glycol copolymer P2
[0036] Polyethylene glycol 10000 (60.0 g, 6 mmol, Mn: 12600, Mw / Mn: 1.06), tri(dibenzylideneacetone)dipalladium(0)-chloroform adduct (93.4 mg, 0.15 mol% for VEC), and phosphine ligand bis(2-diphenylphosphinophenyl)ether (96.8 mg, 0.3 mol% for VEC) were added into the reactor, vacuum dehydrated, and replaced with N2 three times, BEt3 (180 μL of 1 mol·L-1 in THF solution, 0.3 mol% for VEC) and 120 mL of solvent dichloromethane were added, and after the polyethylene glycol was dissolved, 4-vinyl-1,3-dioxolane-2-one (6846.0 mg, 60 mmol, 10 eq.) was added, and the reaction was controlled at 10°C and stirred for 6 hours. After the reaction, the catalyst and the phosphine ligand were removed to obtain a polyethylene glycol-poly(2-vinyl)ethylene glycol copolymer labeled as P2 with a yield of 92%, a vinyl content of 0.46±0.04 mmol / g, a number average molecular weight Mn: 12900, and a polydispersity Mw / Mn: 1.07.
[0037] The NMR spectrum of polyethylene glycol 10000-poly (2-vinyl) glycol copolymer P2 is as follows Figure 2 shown.
[0038] Preparation of polyethylene glycol-poly (2-vinyl) glycol copolymer P3
[0039] Polyethylene glycol 10000 (60.0 g, 6 mmol, Mn: 12600, Mw / Mn: 1.06), tri(dibenzylideneacetone)dipalladium(0)-chloroform adduct (186.8 mg, 0.15 mol% for VEC), and phosphine ligand bis(2-diphenylphosphinophenyl)ether (193.6 mg, 0.3 mol% for VEC) were added into the reactor, vacuum dehydrated, and replaced with N2 three times, BEt3 (360 μL of 1 mol·L-1 in THF solution, 0.3 mol% for VEC) and 120 mL of solvent dichloromethane were added, and after the polyethylene glycol was dissolved, 4-vinyl-1,3-dioxolane-2-one (13692.0 mg, 120 mmol, 20 eq.) was added, and the reaction was controlled at 10°C and stirred for 6 hours. After the reaction, the catalyst and the phosphine ligand were removed to obtain a polyethylene glycol-poly(2-vinyl)ethylene glycol copolymer labeled as P3 with a yield of 85%, a vinyl content of 0.63±0.03 mmol / g, a number average molecular weight Mn: 13800, and a polydispersity Mw / Mn: 1.07.
[0040] The NMR spectrum of polyethylene glycol 10000-poly (2-vinyl) glycol copolymer P3 is as follows Figure 3shown.
[0041] Preparation of polyethylene glycol-poly (2-vinyl) glycol copolymer P4
[0042] Polyethylene glycol 8000 (48.0 g, 6 mmol, Mn: 10000, Mw / Mn: 1.04), tris(dibenzylideneacetone)dipalladium(0)-chloroform adduct (46.7 mg, 0.15 mol% for VEC), and phosphine ligand bis(2-diphenylphosphinophenyl)ether (48.4 mg, 0.3 mol% for VEC) were added into the reactor, vacuum dehydrated, and replaced with N2 three times, BEt3 (90 μL of 1 mol·L-1 in THF solution, 0.3 mol% for VEC) and 96 mL of solvent dichloromethane were added, and after the polyethylene glycol was dissolved, 4-vinyl-1,3-dioxolane-2-one (3423.0 mg, 30 mmol, 5 eq.) was added, and the reaction was controlled at 10°C and stirred for 6 hours. After the reaction, the catalyst and the phosphine ligand were removed to obtain a polyethylene glycol-poly(2-vinyl)ethylene glycol copolymer labeled as P4 with a yield of 96%, a vinyl content of 0.32±0.02 mmol / g, a number average molecular weight Mn: 10100, and a polydispersity Mw / Mn: 1.04.
[0043] The NMR spectrum of polyethylene glycol 8000-poly (2-vinyl) glycol copolymer P4 is as follows Figure 4 shown.
[0044] Preparation of polyethylene glycol-poly (2-vinyl) glycol copolymer P5
[0045] Polyethylene glycol 6000 (36.0 g, 6 mmol, Mn: 8300, Mw / Mn: 1.03), tri(dibenzylideneacetone)dipalladium(0)-chloroform adduct (46.7 mg, 0.15 mol% for VEC), and phosphine ligand bis(2-diphenylphosphinophenyl)ether (48.4 mg, 0.3 mol% for VEC) were added into the reactor, vacuum dehydrated, and replaced with N2 three times, BEt3 (90 μL of 1 mol·L-1 in THF solution, 0.3 mol% for VEC) and 72 mL of solvent dichloromethane were added, and after the polyethylene glycol was dissolved, 4-vinyl-1,3-dioxolane-2-one (3423.0 mg, 30 mmol, 5 eq.) was added, and the reaction was controlled at 10°C and stirred for 6 hours. After the reaction, the catalyst and the phosphine ligand were removed to obtain a polyethylene glycol-poly(2-vinyl)ethylene glycol copolymer labeled as P5 with a yield of 96%, a vinyl content of 0.43±0.04 mmol / g, a number average molecular weight Mn: 8500, and a polydispersity Mw / Mn: 1.03.
[0046] The NMR spectrum of polyethylene glycol 6000-poly (2-vinyl) glycol copolymer P5 is as follows Figure 5 shown.
[0047] Preparation of polyethylene glycol-poly (2-vinyl) glycol copolymer P6
[0048] Polyethylene glycol 4000 (24.0 g, 6 mmol, Mn: 4900, Mw / Mn: 1.07), tris(dibenzylideneacetone)dipalladium(0)-chloroform adduct (46.7 mg, 0.15 mol% for VEC), and phosphine ligand bis(2-diphenylphosphinophenyl)ether (48.4 mg, 0.3 mol% for VEC) were added into the reactor, vacuum dehydrated, and replaced with N2 three times, BEt3 (90 μL of 1 mol·L-1 in THF solution, 0.3 mol% for VEC) and 48 mL of solvent dichloromethane were added, and after the polyethylene glycol was dissolved, 4-vinyl-1,3-dioxolane-2-one (3423.0 mg, 30 mmol, 5 eq.) was added, and the reaction was controlled at 10°C and stirred for 6 hours. After the reaction, the catalyst and the phosphine ligand were removed to obtain a polyethylene glycol-poly(2-vinyl)ethylene glycol copolymer labeled as P6 with a yield of 94%, a vinyl content of 0.73±0.06 mmol / g, a number average molecular weight Mn: 5000, and a polydispersity Mw / Mn: 1.07.
[0049] The NMR spectrum of polyethylene glycol 4000-poly (2-vinyl) glycol copolymer P6 is as follows Figure 6 shown.
[0050] Example 1
[0051] A method for preparing a polyethylene glycol solid-solid phase change material, comprising taking the following raw materials in parts by mass:
[0052] Polyethylene glycol-poly (2-vinyl) glycol copolymer P1 95 parts
[0053] TMPTMP 3 parts
[0054] Irgacure 1173 2 servings.
[0055] The raw materials of each component were melt-blended at 80° C. in a dark room away from light, poured into a mold after being mixed evenly, and irradiated under a 365 nm ultraviolet lamp for 5 minutes to obtain a polyethylene glycol solid-solid phase change material.
[0056] Product confirmation: The infrared spectrum of polyethylene glycol solid-solid phase change material is as follows Figure 7As shown, after the multifunctional thiol crosslinker TMPTMP formed a crosslinked network with PEG-PVEG through a thiol-olefin click chemistry reaction, a characteristic peak of C=O stretching vibration appeared at 1735cm-1 in the spectrum, corresponding to the carbonyl group in TMPTMP, indicating the successful preparation of the solid-solid phase change material.
[0057] Embodiment 2-6
[0058] The method described in Example 1 is adopted, except that: the selection and ratio of raw materials are adjusted, as shown in Table 1, to prepare different polyethylene glycol solid-solid phase change materials respectively.
[0059] Table 1
[0060]
[0061] Performance Test:
[0062] The performance of the polyethylene glycol solid-solid phase change materials prepared in Examples 1-6 was evaluated, including shape stability, heat storage capacity, phase change temperature, mechanical properties, and thermal stability.
[0063] The details are as follows:
[0064] (1) Tensile test:
[0065] The cured materials obtained in Examples 1-4 were subjected to tensile testing using an Instron 3365 electronic universal material testing machine, wherein the tensile test was performed at a speed of 50 mm / min, and the accurate values of modulus, maximum tensile strength and elongation at break were obtained using the average values of five experiments.
[0066] (2) Thermal performance test:
[0067] Thermogravimetric analysis was performed using a NETZSCH thermogravimetric analyzer (TG 209F3) in the range of 50-700°C with a heating rate of 20°C min -1 The thermal stability of the cured material in a nitrogen atmosphere was determined, and the temperature corresponding to the 5% mass degradation was taken as the heat resistance temperature (T 5% ).
[0068] (3) Phase change temperature and heat storage capacity:
[0069] The phase transition temperature and heat storage capacity of the polymer were tested by DSC2000 of TA in the United States. Weigh 5-10 mg of sample in an aluminum crucible, heat it from 40°C to 100°C at a heating rate of 20°C / min in a nitrogen atmosphere, and keep it warm for 3 minutes to eliminate the thermal history. Then cool it to 0°C at a cooling rate of 10°C / min and keep it warm for 2 minutes, and then heat it to 100°C at a heating rate of 10°C / min. Use TA University Analysis software to process the data to obtain the phase transition temperature of the polymer, as well as the latent heat, that is, the heat storage capacity.
[0070] (4) Shape stability test:
[0071] After placing the material on a heating table set at 80°C / 120°C for one hour, observe whether the solid-solid phase change material leaks.
[0072] The test results are shown in Table 2:
[0073] Table 2
[0074]
[0075]
[0076] analyze:
[0077] It can be seen from Table 2 that the polyethylene glycol solid-solid phase change material prepared by the present invention exhibits excellent mechanical properties, shape stability and heat storage capacity, with a latent heat of up to 128 J / g, a maximum tensile strength of more than 9 MPa, and an adjustable phase change, and the cured material exhibits good thermal stability, T 5% The temperature is above 347℃.
Claims
1. A polyethylene glycol solid-solid phase change material, characterized in that: The solid-solid phase change material is a UV light-curable cross-linking material formed by a polyethylene glycol-poly (2-vinyl) glycol copolymer and a polythiol compound.
2. The polyethylene glycol solid-solid phase change material according to claim 1, characterized in that: The polyethylene glycol-poly (2-vinyl) glycol copolymer has a structure shown in the following general formula: Wherein: m, n1 and n2 are all positive integers, and m, n1 and n2 ≥ 1.
3. The polyethylene glycol solid-solid phase change material according to claim 2, characterized in that: The polyethylene glycol-poly (2-vinyl) glycol copolymer can be prepared by the following method: polyethylene glycol containing two hydroxyl groups and 4-vinyl-1,3-dioxolane-2-one or vinyl oxirane are used as raw materials, dissolved in an organic solvent, and reacted at 10-70° C. for 1-6 hours in the presence of a palladium catalyst and a phosphine ligand to obtain the polyethylene glycol-poly (2-vinyl) glycol copolymer.
4. The polyethylene glycol solid-solid phase change material according to claim 3, characterized in that: The polyethylene glycol has a molecular weight of one or more of 500, 1000, 2000, 4000, 6000, 8000, 10000 or 20000.
5. The polyethylene glycol solid-solid phase change material according to claim 4, characterized in that: The polyethylene glycol is selected from polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000 and polyethylene glycol 10000.
6. A method for preparing a polyethylene glycol solid-solid phase change material, characterized in that: The method comprises the following steps: taking the following raw materials according to their mass fractions, mixing them, and reacting them under UV irradiation for 1-100 minutes to obtain a polyethylene glycol solid-solid phase change material; 80-95 parts of polyethylene glycol-poly (2-vinyl) glycol copolymer 3-15 parts of polythiol compound 2 to 5 parts of photoinitiator.
7. The method for preparing a polyethylene glycol solid-solid phase change material according to claim 6, characterized in that: The polythiol compound is selected from one of pentaerythritol tetrakis(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), and 1,4-butanediol bis(thioglycolate).
8. The method for preparing a polyethylene glycol solid-solid phase change material according to claim 6, characterized in that: The photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
Citation Information
Cited By
Preparation method of bio-based degradable polyethylene glycol flexible solid-solid phase change material
CN121108715A